Un Grand amour de Beethoven : [a film script] - Gance, Abel, 1889-1981:::Creator::::::::::::; Dewever, Jean::::::::::::::: (L'Avant-scene; France; Paris, 2022)
Film script including press reviews and filmographies for Un grand amour de Beethoven by Abel Gance, originally released in 1936. Also includes a film script of court-metrage la crise du logement by Jean Dewever.